The Relationship Between Breast Care and the Incidence of Breast Milk Engorgement in Postpartum Mothers at Batara Siang Pangkep General Hospital - Ani; Astrid Yuliandini; Odelia Sulastri (Indonesian Journal of Nursing and Health Care, 2024)
Background: The importance of breast care during breastfeeding is to prevent breast infections such as mastitis or mammary infections.Objective: The aim of this research is to find out whether there is a relationship between breast care and the occurrence of breast milk dams in postpartum mothers.Research Method: This research method uses quantitative research with a Cross Sectional Study approach. The population in this study were all postpartum mothers who were at the Batara Siang Pangkep Regional Hospital, totaling 30 people. The sampling technique in this research is total sampling.Results: The research results showed that of the 30 people sampled, 20 people (66.7%) underwent breast care and 10 people (33.3%) performed well. The results of the study showed that of the 30 people sampled, 19 people experienced breast milk dams (63.3%) and 11 people did not (66.7%).Conclusion: The results of the study show that there is a relationship between breast care and the incidence of breast milk dams.